A Prospective Study of Inflammatory Markers and Risk of Endometriosis. Issue 3 (13th July 2017) - Mu, Fan; Harris, Holly R; Rich-Edwards, Janet W; Hankinson, Susan E; Rimm, Eric B; Spiegelman, Donna; Missmer, Stacey A
Abstract: Much evidence suggests a role for inflammation in the pathogenesis of endometriosis. Although investigators in numerous case-control studies have found elevation of inflammatory markers in patients with endometriosis, results were not consistent, and no prior prospective study is known to exist. We conducted a case-control study nested within the Nurses' Health Study II in which we examined associations between levels of plasma inflammatory markers (interleukin-1 beta, interleukin-6, soluble tumor necrosis factor α receptors 1 and 2, and high-sensitivity C-reactive protein) and the risk of laparoscopically confirmed endometriosis. From blood collections in 1996–1999 and 2007, we ascertained 350 cases patients with incident endometriosis and 694 matched controls. Women with interleukin-1 beta levels in quintiles 2–4 had a higher risk of endometriosis (for the second quintile, relative risk (RR) = 3.30, 95% confidence interval (CI): 1.06, 10.3; for the third quintile, RR = 3.36, 95% CI: 1.09, 10.4; and for the fourth quintile, RR = 4.64, 95% CI: 1.58, 13.6; P for trend = 0.62), which suggested an association beginning at 0.47 pg/mL or greater. A significant nonlinear association with levels of soluble tumor necrosis factor α receptor 2 was observed, with elevated risk of endometriosis at concentrations greater than 3, 400 pg/mL. Plasma interleukin-6, soluble tumor necrosis factor α receptor 1, and high-sensitivity C-reactive protein levels were not associated with endometriosis risk. Further research in larger studies with younger age at blood collection and longer time from blood to surgical diagnosis are required to confirm these associations.